Imunomarcação por calprotectina na caracterização do infiltrado leucocitário transmural no cólon menor equino submetido a isquemia e reperfusão - Isabella Caixeta Winter (2021)
Calprotectin (CP), a protein found in some myeloid lineage cells, is abundant and constitutive in neutrophil cytoplasm. It has been used as inflammatory biomarker that may improve the ability to localize neutrophil and monocyte infiltration in equine intestine during ischaemia and reperfusion (I/R). The goal of this study was immunolocalize CP in myeloid cells to evaluate inflammatory infiltration in equine small colon subjected to I/R injury and its influx into adjacent segments after a complete venous and arterial occlusion model. Archived samples of two intestinal segments from eight animals were used. In one of them, samples were collected at the end of 90 min ischemic period and 90 and 180 min after reperfusion. In the second segment, fragments were collected at 180 min of ischemia and 90 min after reperfusion. A third nonischemic segment served as control in which samples were taken before (CI) and at the end of entire procedure (CF). Inflammatory myeloid cells were labeled by immunohistochemical identification of CP. All histological layers (mucosa, submucosa, muscularis and serosa) were evaluated. Slides were photomicrographed and marked cells were directly counted and expressed in cells/mm2. Mean number of 10 randomly areas from each layer was calculated. Data was analyzed by ANOVA (P ≤ 0.05). There was cell migration through the vessel wall towards tissues in all layers even in the first stage of ischemia. No significant difference between different times of ischemia was found. The number of calprotectin-positive cells increased in all layers after blood flow restoration in at least one of the evaluated times. There was a significant accumulation of neutrophils in submucosa, muscularis and serosa in CF compared to CI. Tissues subjected to I/R and those from CF group showed inflammatory infiltrate predominance in seromuscular layer, with similar magnitude between them. CP immunolocation demonstrated a transmural neutrophilic inflammatory response after ischemic-induced model in small colon with subsequent progression during intestinal reperfusion in all layers, predisposing condition for post-surgical complications such as adhesions, post-operative ileus, enteritis and endotoxemia.